Pengaruh Harga Sewa dan Kualitas Layanan Terhadap Kepuasan Pelanggan Pada Apartemen PT Gunawangsa Merr - Jeni Ayu Tria Praneta; Nuryadi Nuryadi; Komarun Zaman (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to determine the effect of rental prices and service quality on customer satisfaction at Pt Gunawangsa Mapan Sentosa Merr. This study uses primary and secondary data. Data collection techniques using observation and questionnaires. The analysis technique used is quantitative. The results of this study are, Based on the results of partial hypothesis testing there is a significant effect of rental prices on customer satisfaction, and there is also a significant effect of service quality on customer satisfaction. As for simultaneously there is a significant influence of rental prices and service quality on customer satisfaction